Burden of Chlamydia trachomatis infection amongst infertile women compared with pregnant controls in North-central Nigeria - Ogbu, George I.; Anzaku, Stephen A.; Aimakhu, Chris (International Journal of Research in Medical Sciences, 2017)
Background: Female infertility due to tubal damage resulting from pelvic infections including Chlamydia trachomatis is common among women in our environment. The study aimed at determining the prevalence of Chlamydia trachomatis antibody amongst infertile women and to assess the relationship between exposure to Chlamydia trachomatis infection and tubal infertility in Garki Hospital, Abuja, Nigeria. Methods: This was a case control study among 76 infertile patients with tubal occlusion diagnosed with hysterosalpingography and confirmed by laparoscopy compared with 81 pregnant women recruited from the antenatal clinic. Both cases and control were investigated with a study protocol which solicited information on socio-demographic variables, sexual and reproductive risk factors and history of previous pelvic infection. Each subject and control had 5 ml of blood collected for serological assay for Chlamydial antibody titre using the immunocomb Chlamydia trachomatis 1gG kit. The data was analyzed using the SPSS version 20 (IBM, Armonk, NY, USA). A p-value of < 0.05 was considered statistically significant. Results: The prevalence of serum Chlamydial antibody was 57 (75.0%) and 19 (23.5%) among the cases and the pregnant controls respectively (P-value < 0.001). The results showed statistically significant associations between tubal infertility and early age at sexual debut, three or more sexual partners, nulliparity and positive Chlamydia trachomatis antibody titre (P-values < 0.001). Conclusions: The prevalence of Chlamydia trachomatis antibody titre was higher among women with infertility compared to the pregnant controls. The findings suggest that tubal infertility is associated with exposure to Chlamydial trachomatis infection.